Oxford French wordpack - Riqueur, Cathy (Oxford University Press, 2000)
Oxford Wordpacks are ideal resources for language learners of all levels as easy-access aids to vocabulary building. Each volume provides a thematic grouping of essential vocabulary from key language areas: people, house, city, and world. Presented in a double-page spread for easy navigation, these language areas are then broken down and arranged in topics, such as family and friends, holidays and travel, and parts of the body. The words are shown in context, with key phrases being given as well as the vocabulary, and the "Language in Use" section shows how the vocabulary listed is used in daily life